2019
DOI: 10.1371/journal.pgen.1008551
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus calcium-responsive transcription factors regulate cell wall architecture promoting stress tolerance, virulence and caspofungin resistance

Abstract: Aspergillus fumigatus causes invasive aspergillosis, the most common life-threatening fungal disease of immuno-compromised humans. The treatment of disseminated infections with antifungal drugs, including echinocandin cell wall biosynthesis inhibitors, is increasingly challenging due to the rise of drug-resistant pathogens. The fungal calcium responsive calcineurin-CrzA pathway influences cell morphology, cell wall composition, virulence, and echinocandin resistance. A screen of 395 A. fumigatus transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 90 publications
(128 reference statements)
3
64
0
Order By: Relevance
“…Here, we demonstrated that there were increased levels of chitin composition in the cell wall of the ΔcbfA and ΔnctA mutants but not in that of the ΔnctC mutant. We previously demonstrated that the ΔzipD and ΔrlmA mutants have altered chitin composition (22,23). It remains to be determined if the chitin concentration is altered in the ΔnctB, ΔfhdA, ΔznfA, ΔatfA, ΔzfpA, and ΔAFUB_054000 mutants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we demonstrated that there were increased levels of chitin composition in the cell wall of the ΔcbfA and ΔnctA mutants but not in that of the ΔnctC mutant. We previously demonstrated that the ΔzipD and ΔrlmA mutants have altered chitin composition (22,23). It remains to be determined if the chitin concentration is altered in the ΔnctB, ΔfhdA, ΔznfA, ΔatfA, ΔzfpA, and ΔAFUB_054000 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Six of them (ΔcbfA, ΔzipD, ΔnctC, ΔznfA, ΔatfA, and ΔrlmA) have been previously identified as being associated with calcium sensitivity and caspofungin sensitivity and displaying reduced CPE (22,23,28,42). ZipD and RlmA are important for osmotic and cell wall stresses, collaborating for cell wall construction and the activation of several pathways important for osmotic stability (22,23). Here, we demonstrated that there were increased levels of chitin composition in the cell wall of the ΔcbfA and ΔnctA mutants but not in that of the ΔnctC mutant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The propensity of fungal pathogens to cause disease is a complex outcome dependent on a variety of underlying physiological features that facilitate survival in stressful host niches, such as the ability to forage and acquire nutrients (Crawford and Wilson, 2015), to tolerate bombardment from reactive oxygen species (Komalapriya et al, 2015), and to mount a successful defense against (or evade) the host immune system (Jimenez-Lopez and Lorenz, 2013;Hernández-Chávez et al, 2017). Significant progress has been made with respect to understanding the cell and molecular biology of fungal pathogenesis; numerous virulence-related traits and key genes and pathways that regulate these traits have been identified for many fungal pathogens (Navarro-García et al, 2001;Hull and Heitman, 2002;Casadevall, 2006;Liu et al, 2008;Botts et al, 2009;Saputo et al, 2012;Bahn and Jung, 2013;O'Meara et al, 2014;Brown et al, 2014;Bultman et al, 2016;Zaragoza, 2019; de Castro et al, 2019). Similarly, the availability of low-cost, high-throughput genome sequencing has greatly advanced the understanding of genetic variation and population structure for many fungal pathogens (Hu et al, 2008;Fedorova et al, 2008;Butler et al, 2009;Ngamskulrungroj et al, 2009;D'Souza et al, 2011;Hirakawa et al, 2015;Mixão et al, 2019).…”
Section: Introductionmentioning
confidence: 99%